Accreting fluids onto regular black holes via Hamiltonian approach - Abdul Jawad (European Physical Journal C: Particles and Fields, 2017)
Abstract We investigate the accretion of test fluids onto regular black holes such as Kehagias–Sfetsos black holes and regular black holes with Dagum distribution function. We analyze the accretion process when different test fluids are falling onto these regular black holes. The accreting fluid is being classified through the equation of state according to the features of regular black holes. The behavior of fluid flow and the existence of sonic points is being checked for these regular black holes. It is noted that the three-velocity depends on critical points and the equation of state parameter on phase space.